Systematic Importance of Anatomical Characteristics on Selected Dennstaedtiaceae Species from Peninsular Malaysia - Maideen, Haja; Rahman, Norlaila Najwa; Aliah, Nur; Nadhirah , Nurul; Talip, Noraini; Norhazrina, Nik; Bakray, Nur Aqilah; Zohari, Ahmad Fitri; Zainee, Nur Farah Ain; Said, Mohd Nizam Mohd; Khamis, Shamsul; Basir, Nur Syazwani Mohamad (Malaysian Applied Biology, 2024)
Dennstaedtiaceae is a monophyletic fern family widespread in tropical and temperate regions. Data on the anatomy of its species in Peninsular Malaysia are still scarce. Here, we examined anatomical characteristics (leaf venations & shape of steles) among ten species of seven Dennstaedtiaceae genera recorded in Peninsular Malaysia. Two types of vein patterns were observed, most of them having open-leaf venation whereas closed venation was observed only in Histiopteris species. Four types of steles which were ‘U’-shaped, ‘I’-shaped, scattered, and a combination of ‘S’ and ‘W’-shaped and a combination of inverted ‘C’ and ‘W’-shaped’ were observed among all the Dennstaedtiaceae species studied.